Optical Properties of Millimeter-Size Metal-Organic Framework Single Crystals Using Thz Techniques - Singh, D (Elsevier B.V., 2025)
Metal-organic frameworks (MOFs) crystals are promising emerging materials for terahertz (THz) photonics i.e., for THz wave generation through difference frequency or optical rectification and electrooptic detection, including optical components for THz beam steering. The present work reports optical properties of three different non-centrosymmetric single MOF crystals, grown by an innovative solvo-thermal technique with tunable morphology, termed MOF [Zn(3-ptz)2]n (MIRO-101). THz time-domain spectroscopy (TTDS) in the range of 0.25 – 1.5 THz has been used for the measurement of the transfer function, H(ω) of these MOF crystals. Through this experimental function Hexp(ω), optical parameters such as refractive index, nMOF(ω) and absorption coefficient,αMOF(ω) have been calculated for the analysis of the optical properties of this crystal. The results indicate that this MOF crystal offers opportunities for long-term exploration of properties toward the creation of novel nonlinear THz photonics materials, as a THz radiation emitter via Different Frequency Generation (DFG) or Optical Rectification (OR) and Electro-optic (EO) detection via optical sampling, including for its use in optoelectronics, and materials science. © 2024 Elsevier B.V.